La gramática latina y la palabra de Dios - Pérez Rodríguez, Estrella (1992)
The triumph of christianism brought about in the end some necessary changes in Roman traditional education. This paper tries to find out its influence, and basically that of the Holy Scripture, on one of the most important Liberal Arts: grammar. For that purpose the author has thoroughly revised several grammar handbooks written between 7th and 9th centuries A.D. in order to answer the main following questions: what does «christianization» of grammar consist of? to what extend does it spread? How has it developed throughout time?
Keywords: Palabra de Dios (Teología); Lengua latina; Gramática